Las Unlivable Cities A fictional vision of the modern urban experience (2010)
The article portraits the ever more realistic, negative and even sordid vision of the modern city found in many literary works, in comparison with the positive, idealist and aseptic image of the same places mostly provided by architects and urbanplanners in their theoretical discourses. Thus, the author callsfor all professionals involved in the design and development of urban settlements to take into account the more human, real and sensitive vision that writers offer about the urban phenomena when analyzing and rationalizing the city. The article focuses on modern novels and cities, and encompasses a time period from the early eighteen century to the present day. As a final point, after examining the relation between Cityand Literature, the author concludes that for its inhabitants the modern city has been, in general, unlivable.